Utilization of Postnatal among Mothers having under Two years Child in Mahalaxmi Municipality, Lalitpur, Nepal - Paudel, Radha Kumari; Maharjan, Mamata; Shrestha, Sabina (Journal of Advanced Academic Research, 2018)
Postnatal care is a critical phase in the lives of mothers and newborn babies as major changes occur during this period which determines the well-being of mothers and newborns. Adequate utilization of postnatal care can help reduce maternal as well as infant morbidity and mortality. Thus, this study generates the information regarding postnatal care utilization in Lubhu of Mahalaxmi Municipality. This was a descriptive cross-sectional study carried out in a Lubhu of Lalitpur district. The study sample comprised of 130 mothers having unser2 year’s children in year 2017. A pre-tested structured questionnaire was used for data collection. The findings showed that majority of mothers fall under age group 20-29, maximum were from Hindu and Newar ethnicity. This study highlighted more than half (67.7%) mothers utilize the postnatal services. One of the important reasons for not utilizing postnatal services is absence of disease condition in child followed by less knowledge about postnatal services. There was a significant (p=0.018) association between mothers’ education status with utilization of postnatal services. This study concludes that maternal education status affects the maternal utilization of postnatal care services. In order to achieve 100% postnatal care utilization, awareness programs, educational package and other various Postnatal women focused program must be conducted to make them aware about the importance of the utilization of Postnatal services and availability of Postnatal services in different level of health facility.